Boys named Sue disruptive children and their peers - Figlio, David N. (National Bureau of Economic Research, 2005)
"This paper proposes an unusual identification strategy to estimate the effects of disruptive students on peer behavior and academic outcomes. I suggest that boys with names most commonly given to girls may be more prone to misbehavior as they get older. This paper utilizes data on names, classroom assignment, behavior problems and student test scores from a large Florida school district in the school years spanning 1996-97 through 1999-2000 to directly study the relationship between behavior and peer outcomes. I find that boys with female-sounding names tend to misbehave disproportionately upon entry to middle school, as compared to other boys and to their previous (relative) behavior patterns. In addition, I find that behavior problems, instrumented with the distribution of boys' names in the class, are associated with increased peer disciplinary problems and reduced peer test scores, indicating that disruptive behavior of students has negative ramifications for their peers"--National Bureau of Economic Research web site.
Keywords: Erziehung; Psychologie; Behavior disorders in children -- Florida; Boys -- Education; Names, Personal -- Psychological aspects; Problem children -- Education